2016
DOI: 10.1111/eci.12682
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepcidin‐25 with survival after kidney transplantation

Abstract: BackgroundHepcidin is considered the master regulator of iron homoeostasis. Novel hepcidin antagonists have recently been introduced as potential treatment for iron‐restricted anaemia. Meanwhile, serum hepcidin has been shown to be positively associated with cardiovascular disease and inversely with acute kidney injury. These properties may lead to contrasting effects, especially in renal transplant recipients (RTR), which are prone to cardiovascular diseases and graft failure. To date, the role of serum hepci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Several researchers have evaluated the association between serum hepcidin level and mortality risk in CKD patients, but the results are controversial. Some studies have shown the association of hepcidin-25 with increased CV mortality risk in HD patients (15) or with all-cause mortality in diabetic CKD patients (30), while Eisenga et al have not found a predictive role of hepcidin-25 in mortality among patients with kidney transplantation (31). Until now, there has no study to investigate the relationship between serum hepcidin level and mortality in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have evaluated the association between serum hepcidin level and mortality risk in CKD patients, but the results are controversial. Some studies have shown the association of hepcidin-25 with increased CV mortality risk in HD patients (15) or with all-cause mortality in diabetic CKD patients (30), while Eisenga et al have not found a predictive role of hepcidin-25 in mortality among patients with kidney transplantation (31). Until now, there has no study to investigate the relationship between serum hepcidin level and mortality in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation induces hepcidin expression in the liver through cytokines including interleukin (IL)-6 and bone morphogenetic protein (BMP) [ 17 ]. In particular, BMP6, a modulator of the renal response to injury, is a major hepcidin-inducing factor through stimulation of hepatocellular Suppressor against Mothers Against Decapentaplegic (SMAD) production [ 4 ].…”
Section: Id In Ktrs—definitions Epidemiology and Aetiologymentioning
confidence: 99%